DIGITAL MARKETING COMMUNICATION STRATEGY FOR HOTEL EPISODE GADING SERPONG VIA INSTAGRAM @episodegadingserpong - Adindityo Achita Putra; Daniel Susilo; Teguh Dwi Putranto (SEAN Institute, 2023)
In the digital era and the development of social media, an effective digital marketing communication strategy is important for the hospitality industry. This study aims to analyze the digital marketing communication strategy used by Episode Gading Serpong Hotel through Instagram social media. The quantitative content analysis method is used to describe various aspects of the information and quality of the content uploaded by the hotel. Two different coders are used to ensure objectivity in the coding and data collection processes. This study also uses Krippendorf content analysis to determine the characteristics and conclusions of the uploaded message content. The research sample consisted of @episodegadingserpong Instagram uploads from January 2023 to April 2023 which focused on hotel promotions. The results of the study found that the digital marketing communication strategy carried out by Hotel Episode Gading Serpong through Instagram social media was effective in promoting the hotel and attracting consumer attention.